Application of Firefly Algorithm in Voltage Stability Environment Incorporating Circuit Element Model of SSSC with Variable Susceptance Model of SVC. (24th April 2014) - Jebaraj, Luke; Christober Asir Rajan, Charles; Sriram, Kumar
Abstract : This paper proposes an application of firefly algorithm (FA) based extended voltage stability margin and minimization of active (or) real power loss incorporating Series-Shunt flexible AC transmission system (FACTS) controller named as static synchronous series compensator (SSSC) combined with static var compensator (SVC). A circuit model of SSSC and variable susceptance model of SVC are utilized to control the line power flows and bus voltage magnitudes, respectively, for real power loss minimization and voltage stability limit improvement. The line quality proximity index (LQP) is used to assess the voltage stability of a power system. The values of voltage profile improvement, real power loss minimization, and the location and size of FACTS devices were optimized by FA. The results are obtained from the IEEE 14- and 30-bus test case systems under different operating conditions and compared with other leading evolutionary techniques such as shuffled frog leaping algorithm (SFLA), differential evolution (DE) and particle swarm optimization (PSO).